[Save] South Moresby Caravan march and rally, CN [Canadian National Railway] station to Canada Place - Pacific Tribune (photographer) (1986)
Some 1,500 people, led by Haida elders and leaders march through Vancouver streets March 17 in opposition to logging on Lyell Island and other areas in the South Moresby chain of Haida Gwaii.